39‐3: Printed Organic Photodetector Arrays and their use in Palmprint Scanners. Issue 1 (30th May 2018) - Akkerman, Hylke; Peeters, Bart; van Breemen, Albert; Shanmugam, Santhosh; Tordera, Daniel; van der Steen, Jan-Laurens; Kronemeijer, Auke Jisk; Malinowski, Pawel; Roose, Florian De; Cheyns, David; Genoe, Jan; Dehaene, Wim; et al.
Abstract : Using flat‐panel compatible processes we realized 6x8 cm, 200‐ppi active‐matrix imagers with solution‐processed, ultrathin organic photodiodes and demonstrate its performance in a biometric palmprint detector.